Photo Story Usage to Improve Students’ Speaking Skill and Motivation - Sri Ariani; Muhamad Zaenul Husna (Formosa Journal of Sustainable Research, 2022)
This study is aimed to find out the improvement of students` speaking skill by using photo story. This study used Classroom Action Research (CAR) to solve the students’ problem in English speaking. The researchers chose twenty students of the second-grade of MA Darul Aminin NW Aikmual as the participants of the study. Speaking test, interview, and recording were used to collect the data. The data were analyzed by using mix method, namely qualitative and quantitative analyses. The qualitative data were gained by analyzing the interview and observation, and the quantitative data were obtained from the students’ speaking score of pre-test and post-test. The results of the qualitative analysis indicated that the students’ score of post-test was higher than pre-test. Then, the results of the data analysis in quantitative indicated that there was significant different between using photo story and the speaking skill and motivation of students.